Opposite, bidirectional shifts in excitation and inhibition in specific types of dorsal horn interneurons are associated with spasticity and pain post-SCI - Olga Kopach (Nature Portfolio, 2017)
Abstract Spasticity, a common complication after spinal cord injury (SCI), is frequently accompanied by chronic pain. The physiological origin of this pain (critical to its treatment) remains unknown, although spastic motor dysfunction has been related to the hyperexcitability of motoneurons and to changes in spinal sensory processing. Here we show that the pain mechanism involves changes in sensory circuits of the dorsal horn (DH) where nociceptive inputs integrate for pain processing. Spasticity is associated with the DH hyperexcitability resulting from an increase in excitation and disinhibition occurring in two respective types of sensory interneurons. In the tonic-firing inhibitory lamina II interneurons, glutamatergic drive was reduced while glycinergic inhibition was potentiated. In contrast, excitatory drive was boosted to the adapting-firing excitatory lamina II interneurons while GABAergic and glycinergic inhibition were reduced. Thus, increased activity of excitatory DH interneurons coupled with the reduced excitability of inhibitory DH interneurons post-SCI could provide a neurophysiological mechanism of central sensitization and chronic pain associated with spasticity.